FATTY ACIDS, TOCOPHEROLS AND PHYTOSTEROLS IN POMEGRANATE AND PUMPKIN SEED OILS EXTRACTED WITH SUPERCRITICAL CO2 - Baquerizo Canchumanya, Mery (2021)
In the present investigation, the physicochemical characteristics, composition of fatty acids, tocopherols and phytosterols of the oil obtained from granadilla and pumpkin seeds were determined using supercritical CO2 technology. The fruits of granadilla (Passiflora ligularis Juss) and pumpkin (Cucurbita maxima) were obtained and the seeds were extracted, then dehydrated at 60 ° C x 24 hours and subsequent grinding to obtain the oil in a supercritical fluid extractor under the conditions of 350 bar and 50 ° C and CO2 flow of 3mL / min. The composition of fatty acids were analyzed, in the saponifiable fraction of the oils, arachidonic and oleic acid and 82.37 % of unsaturated fatty acids in granadilla seed and oleic, Arachidonic and linoleic acid and 76.01 % of fatty acids were found unsaturated in pumpkin seed and in the unsaponifiable fraction presented α-Tocopherol of 17.85 μg / g in passion fruit and 33.67 μg / g in pumpkin and in the composition of phytosterols, β-sitosterol 13.56 mg / 100g was found in granadilla and 19.50 mg/100g in pumpkin. These oils obtained have physicochemical characteristics of edible oils and have a high percentage of unsaturated fatty acids, so they can be used in formulations in the food and pharmaceutical industry.